Spatiotemporal Evolution and Intensification of Extreme Precipitation Events in Mainland China from 1961 to 2022 - Weimeng Gan; Hao Guo; Ying Cao; Wei Wang; Na Yao; Yunqian Wang; Philippe De Maeyer (Remote Sensing)
Under the context of global warming, extreme precipitation events have become more frequent and intense, causing substantial environmental and societal impacts. Using the daily gridded precipitation dataset (CHM_PRE) for mainland China, this study investigates the spatiotemporal evolution of extreme precipitation events from 1961 to 2022, focusing on regional disparities in frequency, event duration, and total precipitation. Events are further categorized based on peak frequency and the timing of peak intensity to reveal their distinct spatial and temporal characteristics. The results indicate the following: (1) From 1961 to 2022, the frequency of extreme precipitation events across most regions of mainland China exhibited a statistically significant increasing trend, especially in Xinjiang, where the average annual frequency rose by 56 times from 1961–1980 to 2000–2022. (2) Event durations show a general trend, with the most pronounced decline in Southwest China, where the overall duration and the duration above the 90th percentile decreased at Sen’s slopes of −6.4 × 10−2 and −6 × 10−3 days·year−1, respectively. (3) Event intensity has increased, especially in Southeast China, with peak and daily intensities rising at 2.9 × 10−2 mm·year−1 and 1.9 × 10−2 mm·day−1·year−1. (4) Short-duration events dominate Xinjiang, averaging 102 times per year and accounting for 35.58% of all events. (5) Events of varying durations display clear spatial differences: 2-day events are most frequent in Xinjiang, the Tibetan Plateau, Northwest China, and Northern China, while 4-day events are concentrated in Southeast China. Moreover, a nonlinear positive correlation between event duration and total precipitation volume suggests a complex interplay between precipitation persistence and intensity.